RISIKO KEKURANGAN ENERGI KRONIS (KEK) PADA IBU HAMIL DI WILAYAH KERJA PUSKESMAS PAYUNG SEKAKI PEKANBARU - Ayu Sri Pratiwi (Lembaga Penelitian dan Penerbitan Hasil Penelitian Ensiklopedia, 2020)
The prevalence of maternal MUAC in Indonesia in 2013 is equal to 24.2%. In Riau province that is equal to 26%. This shows that there is still a high-risk pregnant women KEK. The purpose of this study to determine risk factors associated with Chronic Energy Deficiency (CED) In pregnant women at Puskesmas Payung Sekaki Pekanbaru Year 2014 Sectional Study Analytical study type (Analytic Cross Sectional) with a sample of 211 people. Measuring instrument using a questionnaire, risk is measured by the KEK measurement method, while the 2 x 24-hour recall was measured using NutrySurvey program to determine the level of intake of protein, carbohydrates and Energy pregnant women. Data analysis was performed using univariate, bivariate chi-square test and multivariate logistic regression Ganda. The results showed no causal link between protein intake POR 1080.202 (95% CI: 14.094-82788.218), carbohydrate intake POR 548 714 (95% CI: 12.265-24548.600), energy intake POR 164 082 (95% CI: 13.061-2061.373), and family income POR 10,288 (95% CI: 2296-46100) with KEK risk in pregnant women. For that the health workers are expected to perform routine counseling weekly, monthly, and yearly on nutrition for pregnant women in any urban villages in Puskesmas Payung Sekaki and doing it for free supplementary feeding to pregnant women who are malnourished so good maternal nutritional status, and for family income should be entered into collaboration and multi-sector partnerships in small business development community to improve the community's economy.